Damping of multimodal power system oscillations by FACTS devices using non-linear Takagi-Sugeno fuzzy controller - Dash, P (2003)
The paper presents a non-linear Takagi-Sugeno fuzzy controller for flexible AC transmission system (FACTS) devices in a multi-machine power system. This controller uses a numerical consequent rule base, which can be either linear or non-linear producing control gain variations over a very wide range. This controller is expected to be more robust and effective in damping electromechanical oscillations of the power system compared to the conventional PI controller. Digital simulations of a multi-machine power system, with series connected FACTS devices like UPFC, TCSC and TCPST, etc. subjected to a wide variety of transient disturbances validate the efficiency of the new approach in damping multimodal oscillations. (C) 2003 Elsevier Science Ltd. All rights reserved.